Buddhist community development guidelines : A case study of Banthawatburi community, village no. 3 Wat nuea udon chaisit, Thong thani subdistrict, Thawat buri district Roi-et province - Dhammadhinno , Phraathikan Thanabodee; Suanmafai , Phaitoon; Addhasitdho, Pharkhruphalad Sommai (Journal of Graduate Saket Review, 2023)
The study consisted of the following objectives: 1) to investigate the present conditions of Ban Thawat Buri Community, Moo 3, Wat Nuea Udon Chaisit, Thong Thani Subdistrict, Thawat Buri District Roi Et Province; 2) to study the community development process based on the Buddhist way of Ban Thawat Buri Community, Moo 3, Wat Nuea Udon Chaisit, Thong Thani Subdistrict, Thawat Buri District Roi Et Province; and 3) to explore the guidelines for community development of Ban Thawat Buri Community, Moo 3, Wat Nuea Udon Chaisit, Thong Thani Subdistrict, Thawat Buri District Roi Et Province. The study applied a qualitative research method by studying documents and interviews conducted on a field trip. From the study, it is found as follows: the plains next to the Chi River comprise the majority of the Ban Thawat Buri Community where most people are farmers. The occupations of people in the community are divided into 5 groups with 4 village funds. The community development process of Ban Thawat Buri Community is based on Buddhist teachings that are used to making a living in all 5 groups: 1) Sufficiency Agriculture Group based on ‘Bowon’ (village, temple, and school); 2) Temple Development Volunteer Group; 3) ‘Glong Yao Wat Nuea’ Group; 4) Agricultural Processing Group; and 5) Ornamental Plant Breeding Group. The making a living in all these 5 groups must be based on Sammā-ājīva (right livelihood whether physically, verbally, or mentally), Saṅgahavatthu (four bases of social solidarity), and Iddhipāda (four paths of accomplishment). The guidelines for community development of Ban Thawat Buri Community include brainstorming for knowledge seeking and turning it into a strategic plan or development plan as a means to practice for agencies and organizations. The plan also acts as the starting point or first thing to do when it comes to working together, holding training to impart knowledge, engaging community members, and creating a moral cycle in the community.